Respostas de cultivares de soja e otimização de população de milho em dois ambientes agrícolas contrastantes no Rio Grande do Sul - Baron, Felipe Arthur (2024)
Early sowing and the use of cultivars with an early cycle are essential for the rapid establishment of second-crop corn. The delay in soybean sowing places corn in a period with a high chance of water deficit in the middle to the end of the cycle. Adjusting seeding density is one of the most important factors in defining the productivity potential of corn crops. The objective of the study was to analyze the expression of agronomic components of soybean and corn crops through adjustments in cultural practices for the optimal positioning of genotypes in contrasting environments. the influence of the sowing time on the cultivars DM53i54 IPRO, DM65i63 IPRO and DM59i58 IPRO in Condor-RS in the 2018/19 and 2022/23 harvests is respectable, as well as the cultivars DM 57i52 IPRO, BMX Zeus IPRO, M6100 XTD, NEO 590 I2X, AS 3595 I2X and BMX Fibra IPRO in São Borja-RS, in the 2022/23 harvest. The cultivars DM53i54 IPRO and DM59i58 IPRO expressed the highest grain yield in the first and second sowing season, respectively, in the 2018/2019 harvest in Condor-RS. The DM53i54 IPRO and DM59i58 IPRO cultivars expressed the best performance in the first sowing season in the 2022/2023 harvest in Condor-RS, with the DM53i54 IPRO cultivar also being the most productive in the second season for this harvest. The cultivar M6100 The influence of sowing density on corn cultivation was evaluated in Boa Vista das Missões-RS (2015/2016 harvest), with the presence of supervision, and Condor-RS (2018/2019 harvest), in a rainfed system. The densities evaluated were: 60, 75, 90, 105 and 120 thousand seeds ha-1. The presence of transparency promoted greater stability of corn agronomic components when faced with increased seeding density. Adjustments to 94.71 and 82.19 thousand seeds per hectare made it possible to achieve the highest grain yields in Boa Vista das Missões-RS and Condor-RS.